Transient conformational remodeling of folding proteins by GroES—individually and in concert with GroEL - Moparthi, Satish Babu (Springer Berlin Heidelberg, 2013)
The commonly accepted dogma of the bacterial GroE chaperonin system entails protein folding mediated by cycles of several ATP-dependent sequential steps where GroEL interacts with the folding client protein. In contrast, we herein report GroES-mediated dynamic remodeling (expansion and compression) of two different protein substrates during folding: the endogenous substrate MreB and carbonic anhydrase (HCAII), a well-characterized protein folding model. GroES was also found to influence GroEL binding induced unfolding and compression of the client protein underlining the synergistic activity of both chaperonins, even in the absence of ATP. This previously unidentified activity by GroES should have important implications for understanding the chaperonin mechanism and cellular stress response. Our findings necessitate a revision of the GroEL/ES mechanism. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (doi:10.1007/s12154-013-0106-5) contains supplementary material, which is available to authorized users.